Alpha-1 chain of human haptoglobin as viability marker of in vitro fertilized human embryos: information beyond morphology. (4th March 2019) - Montskó, Gergely; Gödöny, Krisztina; Herczeg, Róbert; Várnagy, Ákos; Bódis, József; Kovács, Gábor L.
ABSTRACT: Only one third of the in vitro fertilization treatments result in successful delivery following morphological viability assessment worldwide. A paper by Montskó et al. (2015) describes the identification of the alpha-1 chain of human haptoglobin as a potential marker of embryo viability. Using mass spectrometry, the concentration of the haptoglobin alpha-1 chain was determined in spent culture media samples of in vitro fertilized embryos and correlation was found with the outcome of the respective transfer. In the present study we investigated, whether the concentration of haptoglobin alpha-1 chain shows any correlation with morphological scores to clarify whether levels of the alpha-1 chain provide additional information on embryo viability unnoticed by the morphological assessment. In the study, pregnancy and live birth rates were examined in 143 transferred samples of 86 patients, retrospectively. Two sample groups were created. The control group contained embryos classified as 'good' or 'fair' based on the Istanbul Consensus Criteria System, while the double-assay group contained embryos assessed as 'good' or 'fair' by the morphological evaluation and as 'viable' by the haptoglobin assay. Clinical pregnancy rate was 30.2% in the control group, while 47.6% in the group scored parallel with morphological criteria and proteomic analysis ( p  < 0.05). The increased clinical pregnancy rate observed in the double-assayed group can be attributed to decreased false-positivity of the double assay. Abbreviations : IVF: in vitro fertilization; SEC: spent embryo culture medium; HSA: human serum albumin; Hpt: haptoglobin; HptA1: haptoglobin alpha-1 chain; ICCS: Istanbul Consensus Criteria System; BMI: body mass index; ICSI: intracytoplasmic sperm injection